O1A.3 Occupational insecticide exposure, glycemic regulation and bronchoconstriction: preliminary results from a short-term cohort study among small-scale farmers in uganda. (April 2019) - Rune Hassan Hansen, Martin; Jørs, Erik; Sandbæk, Annelli; Sekabojja, Daniel; Ssempebwa, John; Mubeezi, Ruth; Staudacher, Philipp; Fuhrimann, Samuel; Schlünssen, Vivi
Abstract : Introduction: Epidemiological studies have suggested associations between exposure to some classes of non-persistent insecticides, airways obstruction (Doust et al, 2014) and diabetes mellitus (Evangelou et al, 2016). Yet the evidence is limited by cross-sectional study designs and exposure metrics based on self-reported information only. The purpose of this study is to investigate these associations in a strong study design employing objective exposure metrics. Methods: From September 2018 to February 2019, we are conducting a short-term cohort study in a population of 370 small-scale farmers in Uganda, half of which are conventional farmers and the other half working towards organic certification. We examine participants before, during and after the October-November agricultural pesticide-spraying season. In each study round, participants perform spirometry, and glycemic regulation is assessed by analysis of glycated aemoglobin A (HbA1c) as well as fasting plasma glucose for a subgroup. Detailed questionnaire-based information on pesticide usage (frequency, intensity, duration, specific compounds, personal protective equipment etc.) is used to construct an internal task-exposure matrix. The task-exposure matrix will be validated by erythrocyte choline esterase (AchE) activity as a proxy for organophosphate and carbamate exposure, as well as passive pesticide samplers (silicone wristbands) worn by participants between the study rounds. Results and discussion: The baseline (pre-spraying season) data collection is finalized. Data collection for the two rounds of follow-up (during/after the spraying season) is ongoing. At the conference, we will present the first results on temporal changes across the spraying season in AchE and associations with glycated aemoglobin A, fasting plasma glucose and lung function. References: Doust, et al. Is pesticide exposure a cause of obstructive airways disease?European Respiratory Review2014June 1;23(132):180–92. Evangelou, et al. Exposure to pesticides and diabetes: A systematic review and meta-analysis. Environment International2016May 1;91:60–8.